2021
DOI: 10.3390/ijms23010383
|View full text |Cite
|
Sign up to set email alerts
|

STOP1 Regulates LKS1 Transcription and Coordinates K+/NH4+ Balance in Arabidopsis Response to Low-K+ Stress

Abstract: Potassium and nitrogen are essential mineral elements for plant growth and development. The protein kinase LKS1/CIPK23 is involved in both K+ and NH4+ uptake in Arabidopsis root. The transcripts of LKS1 can be induced by low K+ (0.1 mM) and high NH4+ (30 mM); however, the molecular mechanism is still unknown. In this study, we isolated the transcription factor STOP1 that positively regulates LKS1 transcription in Arabidopsis responses to both low-K+ and high-NH4+ stresses. STOP1 proteins can directly bind to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Additionally, this pleiotropy for STOP1 regulation of gene networks can involve different transcription factor partners for STOP1, such as TCP20 for NRT1,1 under N deficiency and MED16 for ALMT1 expression under low P/high Fe ( 56 ). Moreover, STOP1/CIPK23 enhances root K + uptake by activating the high-affinity K + transporters, HAK and AKT1, to help plant acquire K + from low K soils ( 29 , 32 ). Thus, STOP1 may act as a hub to integrate various root nutrient and toxic metal stress responses, which allow plants to manage the appropriate root growth responses that modify RSA under complex environments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, this pleiotropy for STOP1 regulation of gene networks can involve different transcription factor partners for STOP1, such as TCP20 for NRT1,1 under N deficiency and MED16 for ALMT1 expression under low P/high Fe ( 56 ). Moreover, STOP1/CIPK23 enhances root K + uptake by activating the high-affinity K + transporters, HAK and AKT1, to help plant acquire K + from low K soils ( 29 , 32 ). Thus, STOP1 may act as a hub to integrate various root nutrient and toxic metal stress responses, which allow plants to manage the appropriate root growth responses that modify RSA under complex environments.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, STOP1 also may play important roles in the alteration of RSA for the better acquisition of P and K. Under P-deficient conditions in acid soils, where iron (Fe 3+ ) availability is often excessive, STOP1 turns on the expression of the AL-ACTIVATED-MALATE-TRANSPORTER1 ( ALMT1 ), first identified as a major Al tolerance gene, and the root released malate solubilizes Fe 3+ from the Arabidopsis root cell wall and facilitates its accumulation into cells of the root tip, where it is involved in inhibition of primary root growth under low P. This presumably alters the emphasis of the RSA to more efficient P uptake by the formation of more shallow LRs, where more of the phosphate resides ( 30 , 31 ). In addition, recent STOP1 studies have identified other pleiotropic roles for it in nutrient acquisition, including transcriptional regulation of CIPK23 , which in turn phosphorylates the high-affinity K + transporters, HIGH-AFFINITY-K + -TRANSPORTER5 (HAK5) and ARABIDOPSIS-K + -TRANSPORTER1 (AKT1), leading to enhancement of root potassium uptake ( 29 , 32 ). The STOP1/CIPK23 complex is also involved in ammonium uptake by activation of AMMONIUM-TRANSPORTER1 under phosphorus deficiency ( 33 ).…”
mentioning
confidence: 99%
“…STOP1 localizes to the nucleus and up-regulates the expression of many genes involved in low pH tolerance and Al resistance ( Sawaki et al., 2009 ). Recent studies revealed that STOP1 is essential for low-O 2 ( Enomoto et al., 2019 ), low-Pi ( Balzergue et al., 2017 ; Mora-Macias et al., 2017 ), low-K ( Wang et al., 2021 ), drought and salt tolerance ( Sadhukhan et al., 2019 ) in Arabidopsis. These findings suggest that STOP1 functions as a central factor in modulating the response to coexisting environmental stresses in acid soils.…”
Section: Overview Of Stop1 and Stop1-like Proteinsmentioning
confidence: 99%
“…AtSTOP1 modulates the transcription of AtHAK5 (High-affinity K + transporter 5) ( Sawaki et al., 2009 ; Nakano et al., 2020 ), AtSULTR3;5 (Sulfate transporter 3;5) ( Sawaki et al., 2009 ), H + -coupled high-affinity NO 3 - symporter gene AtNRT1.1 (Nitrate transporter 1.1) ( Fang et al., 2016 ; Ye et al., 2021 ) and AtCIPK23 (CBL-interacting protein kinase 23) ( Sawaki et al., 2009 ). AtCIPK23 additionally regulates the activity of AtHAK5 ( Ragel et al., 2015 ; Wang et al., 2021 ), AtAKT1 (Arabidopsis K + transporter 1) ( Li et al., 2006 ; Xu et al., 2006 ), AtNRT1.1 ( Liu and Tsay, 2003 ; Leran et al., 2015 ), and AtAMTs (Ammonium transporters) ( Straub et al., 2017 ; Wang et al., 2021 ) through phosphorylation to influence ion uptake, overcome rhizosphere acidification and establish a favorable cellular pH. Besides, AtSTOP1 promotes the expression of AtTDT (tonoplast dicarboxylate transporter) to increase the concentration of dicarboxylate and, hence, enhance the capacity to produce OH - to regulate the pH homeostasis in the cytosol ( Hurth et al., 2005 ).…”
Section: Stop1 and Stop1-like Proteins Mediated Low Ph Tolerancementioning
confidence: 99%
See 1 more Smart Citation